The Effect of Warm Compresses on Reducing Dysmenorrhea Pain in Women of Childbearing Age at the Bungursari Health Center, Purwakarta Regency, Indonesia - Rahmita Budiarti; Lia Yulianti (Archives of The Medicine and Case Reports, 2023)
Menstrual disorders that are often experienced by women such as lower abdominal pain, irregular menstruation, low back pain, and one of them is dysmenorrhea. Dysmenorrhea is a condition where women experience pain during menstruation which has a bad effect causing disruption to carrying out daily activities because of the pain they feel. This condition can last 2 days or more than the length of menstrual days each month. There are several ways that can be done to treat pain non-pharmacologically, including massage therapy, elevating the feet from the body, exercising, regulating diet and applying warm compresses. This study aimed to determine the effect of warm compresses on reducing menstrual pain (dysmenorrhea) in women of childbearing age at the Bungursari Health Center. This study was an experimental research with a one group pretest posttest design approach, obtained by 30 respondents. The sample in this study were all women of childbearing age who experienced menstrual pain (dysmenorrhea) in the Bungursari Health Center, Purwakarta Regency. Warm compresses can reduce menstrual pain (dysmenorrhea) at the Bungursari Health Center, p value=0.002 < Î± (0.05). Giving warm compresses can reduce menstrual pain in women of childbearing age (WUS). It is expected that the public will gain knowledge about menstrual pain (dysmenorrhea) and can use warm compress therapy as a way to deal with menstrual pain (dysmenorrhea).